Are African primary physicians suspicious enough? Challenges of multiple myeloma diagnosis in Africa - Erick Thokerunga; Christopher Ntege; Abdullahi Omar Ahmed (SpringerOpen, 2021)
Abstract Background Multiple myeloma is a hematological malignancy of plasma cells belonging to a spectrum of monoclonal protein-secreting disorders known as paraproteinemias. It is classically characterized by accumulated plasma cells in the bone marrow, renal insufficiency, hypercalcemia, and bone lesions (CRAB). Despite studies in the USA indicating that the incidence of multiple myeloma is twice as much in Americans of African descent compared to white Americans and those of Asian descent, African countries have some of the lowest incidence rates and prevalence of the cancer. It is generally thought that this is not entirely factual given the paucity of research into the cancer in sub-Saharan Africa, coupled with other diagnostic challenges such as economic hardships, and poor health-seeking behaviors. In this mini review, we explored the state of multiple myeloma diagnosis across sub-Saharan Africa, outlining the challenges to diagnosis and proposing possible solutions. Main body Due to the lack of routine checkups in people > 40 years across sub-Saharan Africa, monoclonal gammopathy of undetermined significance (MGUS) and smoldering multiple myeloma (SMM) are often accidentally diagnosed. This is due to a very low awareness of multiple myeloma among primary care clinicians and the general population. Other major challenges to multiple myeloma diagnosis across Africa include a chronic shortage of human resource (pathologists, cytotechnologists, and histotechnologists), and a prohibitive cost of diagnostic services that discourages early diagnosis. Conclusion To improve multiple myeloma diagnosis in Africa, a systems approach to thinking among policy makers, philanthropic organizations, and oncologists must be adopted. Governments must invest in health insurance coverage for cancer patients concurrently with heavy investments in human resource training and diagnostic infrastructure scale up. Creative approaches such as digital pathology, online training of clinicians, research and capacity building collaborations among African institutions, European and American institutions, and pharmaceutical companies as seen with other cancers should be explored for multiple myeloma too.